2024
DOI: 10.1177/11795549241244783
|View full text |Cite
|
Sign up to set email alerts
|

MiR-339-5p Inhibits Ferroptosis by Promoting Autophagic Degradation of FTH1 Through Targeting ATG7 in Liver Cancer Cells

Fei Cao,
Weiyuan Hao,
Weiren Liang
et al.

Abstract: Background: Liver cancer has a high incidence and mortality rate worldwide, and there is an urgent need to identify new therapeutic strategies and predictive targets to improve the clinical outcomes of advanced liver cancer. Ferroptosis holds promise as a novel strategy for cancer therapy. Epigenetic dysregulation is a hallmark of cancer, and noncoding RNAs are tightly involved in cell fate determination. Therefore, we aimed to identify a novel ferroptosis regulator from aberrantly expressed microRNAs that may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…28 Besides, miR339 inhibits ferroptosis by promoting autophagic degradation of FTH1 through targeting ATG7 in liver cancer cells. 29 However, whether miR339 acts as a radiosensitizer to facilitate therapeutic efficacy remains unclear. Here, we found that miR339 was involved in stem cell division and DNA checkpoint signaling pathways based on our ESCC cohort, 30 and USP8, a direct target of miR339, promotes radioresistance by maintaining ESCC cell stemness and inhibiting DNA damage in vitro.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…28 Besides, miR339 inhibits ferroptosis by promoting autophagic degradation of FTH1 through targeting ATG7 in liver cancer cells. 29 However, whether miR339 acts as a radiosensitizer to facilitate therapeutic efficacy remains unclear. Here, we found that miR339 was involved in stem cell division and DNA checkpoint signaling pathways based on our ESCC cohort, 30 and USP8, a direct target of miR339, promotes radioresistance by maintaining ESCC cell stemness and inhibiting DNA damage in vitro.…”
mentioning
confidence: 99%
“…Recently, the miR339/KEAP1/Nrf2 axis was found to promote the macrophage M1-to-M2 transition and ischemic flap survival . Besides, miR339 inhibits ferroptosis by promoting autophagic degradation of FTH1 through targeting ATG7 in liver cancer cells . However, whether miR339 acts as a radiosensitizer to facilitate therapeutic efficacy remains unclear.…”
mentioning
confidence: 99%